Years of healthy life lost by the population of Medellin, 2006-2012 - Grisales-Romero, Hugo; Marín, Diana; González-Gómez, Difariney; Grajales, Isabel Cristina; Porras Cataño, Sandra Milena; Colorado-Betancur, Leydy Johana; Lopera Velásquez, Verónica María (Papeles de Población, 2018)
The burden of disease in the population of Medellin between 2006 and 2012 was determined by the three broad cause groups following the methodology of the Global of burden of disease study. Official mortality information was used for the calculation of potential years of life lost (YPLL). The registered information referring morbidity were used for the calculation of the years of life adjusted by disability (YLD). 87 per cent of the Disability-Adjusted Life Year (DALY), sum of the YPLL and the YLD, was due to the disability. Non-communicable diseases and accidental injuries contributed the largest number of alerts. The role of non-communicable diseases yet increase in Comorbidities of high cost.